2010
DOI: 10.1167/iovs.09-4821
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Medication, Statins, and the Risk of Glaucoma

Abstract: PURPOSE. To examine whether treatment with oral blood-pressure-lowering medication or statins influences the risk of glaucoma. METHODS. This study was a case-control investigation, nested within a computerized primary care database of 177 general practices across the United Kingdom; 8778 cases diagnosed and/or treated for glaucoma between 2000 and 2007, and 8778 glaucoma-free controls matched for age, sex, and practice. Odds ratios for treatment with oral antihypertensives (including selective beta(1) and nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 36 publications
2
48
1
7
Order By: Relevance
“…In conclusion, we respectfully disagree with inclusion of the case-control studies by Owen et al 2 in both the systematic review and meta-analysis and the cross-sectional study by Khawaja et al 3 in the systematic review. In carrying out the meta-analysis, there is still room for discussion on the assignment of suspected glaucoma to incidence or progression outcome.…”
Section: Figurecontrasting
confidence: 73%
“…In conclusion, we respectfully disagree with inclusion of the case-control studies by Owen et al 2 in both the systematic review and meta-analysis and the cross-sectional study by Khawaja et al 3 in the systematic review. In carrying out the meta-analysis, there is still room for discussion on the assignment of suspected glaucoma to incidence or progression outcome.…”
Section: Figurecontrasting
confidence: 73%
“…Thus, hypertension was defined as a patient receiving ≥2 antihypertensive compounds. Because previous studies have shown a decreased risk of glaucoma in patients treated with systemic β-blockers or calcium channel inhibitors, 16,23,[35][36][37] it seems reasonable to interpret the present observed reduction of the risk of developing glaucoma in patients treated with antihypertensive as a causal effect of particular antihypertensive drugs. …”
mentioning
confidence: 48%
“…Previous studies have shown an association between antihypertensive medication and glaucoma (but the evidence is still scarce). [19][20][21]35 However, no previous study has investigated the causal effect of antihypertensive medication on glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on systemic medications and IOP indicated that lower IOP is associated with systemic β-blockers9 10 and nitrates10 and revealed effects that included an increased risk of developing glaucoma for statins11 and calcium channel blockers 12. In a study of a UK primary care database, oral selective β 1 -blocker intake was associated with a reduced risk of developing glaucoma 13. However, the evidence remains inconclusive regarding the effect of systemic cardiovascular medications on IOP.…”
Section: Introductionmentioning
confidence: 99%